Vaccination for 2009 pandemic H1N1 influenza A did not induce conserved epitope-specific memory CD8 T cell responses in HIV+ northern Thai children. Issue 38 (11th September 2015) - Chawansuntati, Kriangkrai; Aurpibul, Linda; Wipasa, Jiraprapa
Abstract: The influenza virus causes severe illness in susceptible populations, including children and people living with human immunodeficiency virus (HIV). Here, we investigated cell-mediated immune responses (CMI) against influenza CD8 T cell conserved epitopes in HIV-infected (HIV+) northern Thai children following the 2009 pandemic H1N1 influenza A vaccination. Sixty HIV+ children were vaccinated with two doses of the 2009 pandemic influenza vaccine and their CD8 T cell responses were assessed. We found no significant differences in the increase of cytokines-producing and CD107a-expressing CD8+ T cells or CD8+ memory T cells in response to pooled conserved epitopes stimulation in vitro between children with different serologic responses to the vaccine at all time points of the study. Our results suggest that the 2009 pandemic H1N1 vaccine did not induce the conserved epitope-specific immune responses in HIV+ children. Vaccine design and vaccination strategy against influenza in these populations warrant further studies.